The Impact of Public Opinion Pressure on Construction Company Green Innovations: The Mediating Effect of Leaders' Environmental Intention and the Moderating Effect of Environmental Regulation - Wang, Bo; Han, Shan; Ao, Yibin; Liao, Fangwei; Wang, Tong; Chen, Yunfeng (Frontiers in Psychology, 2022)
Media has paid more attention recently on environmental issues caused by construction companies which imposes public opinion pressure on construction companies and could potentially impact their decision-making processes for green innovations. However, research on the relationship between public opinions pressure and construction company green innovation behavior is still limited. To understand how such public opinions pressure can impact construction companies’ green transition and formulate advice accordingly, it is necessary to use empirical data to find the correlations.Therefore, this research has gathered questionnaire data of the construction companies in Chengdu-Chongqing economic circle of China to study the influencing mechanism of environmental public opinion pressure on enterprise green innovation behavior, analyzes the realization path of leaders’environmental intention as a mediating variable in the impact of environmental public opinion pressure on enterprise green innovation behavior, and reveals the role boundary of environmental regulation as a moderating variable in the impact of environmental public opinion pressure on enterprise green innovation behavior.The results show that environmental public opinion pressure has a significant positive impact on enterprise green innovation behavior. More specifically, enterprise green innovation behavior is affected by leaders’ environmental intention and the latter plays a partial mediating role between environmental public opinion pressure and enterprise green innovation behavior. Environmental regulation also enhances the sensitivity of companies to environmental public opinion pressure, and therefore can significantly strengthen the relationship between environmental public opinion pressure and enterprise green innovation behavior. Further research find that, compared with incentive-based environmental regulations, mandatory environmental regulations make companies more sensitive to environmental public opinion pressure and has a more significant positive moderating effect. The research conclusions could be used to provide theoretical reference with empirical data for accelerating the green innovation transformation and promoting the high-quality development in the construction industry.